Implications and Challenges of China’s Supremacy on the Global Rare Earths Market - ANA-CRISTINA BÂLGĂR (Global Economic Observer, 2021)
China’s spectacular economic development over the last four decades or so, and its atypical evolution during this process placed the country both at the forefront of the global rare earth trade, and at the centre of international concerns and debates on the implications this ascent has on the regulations governing global trade. Now an uncontested contemporary reality, China’s supremacy on the global rare earth market has fuelled the fears of strongly industrialised countries for the future security of the supply of these raw materials, as a direct result of the extent to which Chinese governmental authorities will from now on choose to comply or not to comply with the international trade rules and practices in force. In these conditions, our article seeks to provide an overview of the evolution of Chinese policies in the field of rare earths, of how they helped transform natural resources endowment into a competitive advantage, and of the recent trends on this global market on which China is the leader.